116 Effect of Annual Hospital Procedure Volume on Outcomes After Mechanical Thrombectomy in Acute Ischemic Stroke Patients: An Analysis of 13 502 Procedures. (August 2016) - Jani, Vishal B.; To, Chiu Yuen; Patel, Achint; Kelkar, Prashant S.; Richards, Boyd; Fessler, Richard D.
Abstract : INTRODUCTION: We aim to analyze the impact of annual hospital volume on outcomes of endovascular mechanical thrombectomy (EMT) for acute ischemic stroke (AIS). In the recent past, increasing number of hospitals are acquiring capabilities for EMT procedure for the treatment of AIS, including some low-volume centers. There are few data on outcomes comparing these hospitals with high-volume centers. METHODS: We queried the National Inpatient Sample from 2008 to 2011 using International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9 CM) diagnosis codes 433 to 437.1 in any position for AIS. Adult patients with ICD-9-CM procedure code 39.74 for mechanical thrombectomy were included in the final cohort. Annual hospital procedure volume was computed using the unique hospital identification number (HOSPID) and was dichotomized corresponding to <10 (low) and ≥10 (high) procedures per year. Comorbid conditions were defined using the Deyo modification of the Charlson Comorbidity Index (CCI). Primary outcomes were in-hospital mortality and any complications (combination of in-hospital mortality, intracerebral hemorrhage, vascular complications). We built hierarchical 2-level models adjusted for multiple confounding factors, with HOSPID incorporated as random effects in the model. RESULTS: A total of 13 502 procedures were available for analysis, of which 3352 (24.8%) were performed in low-volume hospitals. Overall in-hospital mortality and any complications were higher in low-volume hospitals 25.6% vs 21.1% ( P < .001) and 34.2% vs 30.2% ( P < .001), respectively. However, in a multivariate hierarchical model, low-volume hospitals were not associated with higher odds of in-hospital mortality and any complications (odds ratio [OR], 0.95; 95% confidence interval [95% CI], 0.74-1.23, P = .684) and (OR, 0.96; 95% CI, 0.76-1.21, P = .720). Similar results were observed even in sensitivity analysis. CONCLUSION: Although the proportion of in-hospital mortality was higher among patients undergoing EMT at low-volume centers, risk-adjusted odds of in-hospital mortality were similar to high-volume EMT centers. Our findings raise important question on this phenomena for EMT procedure for AIS and warrant further studies.